Arg-Gly-Asp-modified elastin-like polypeptide regulates cell proliferation and cell cycle proteins via the phosphorylation of Erk and Akt in pancreatic β-cell. Issue 9 (September 2020) - Hwang, Yeo Jin; Jung, Gwon-Soo; Jeon, Won Bae; Lee, Kyeong-Min
Abstract: Objective: Enhancement of β-cell proliferation plays an important role in maintaining β-cell mass and function, and in improving pancreatic β-cell survival before transplantation. Extracellular matrix (ECM) components increase the adhesion and proliferation of β-cells, and the RGD-modified elastin-like polypeptide (RGD-ELP, REP) has been described as a bioactive matrix. In this study, we investigated whether REP could enhance β-cell adhesion and proliferation and elucidated the signaling pathways involved. Methods: We investigated the effect of REP on cell adhesion, proliferation and insulin secretion via assays using Rin-m and rat islets. Crystal violet, CCK-8, and BrdU assay, FACS, western blot, real time q-PCR analyses and insulin ELISA were examined. To explain the associated mechanisms, phosphorylation of Akt and extracellular signal-regulated kinase (Erk) were measured. Results: REP more increased the adhesion, proliferation and survival of Rin-m cells compared to elastin-like poly peptide (ELP) without RGD-motif. The enhancement of β-cell proliferation by REP was associated with increased cyclin D1, cyclin D2 and cdk6, and decreased p27 levels. When β-cells were cultured on REP, Erk and the phosphatidylinositol 3-kinase (PI3-kinase) downstream effector, Akt was stimulated. Treatment with the Erk pathway inhibitor and PI3-kinase inhibitor decreased REP-induced β-cell adhesion and proliferation, and regulated REP-induced cell cycle proteins. Additionally, REP increased the mRNA and protein levels of insulin and its transcription factor, PDX-1, and insulin secretion. Conclusions: Our results demonstrate that the up-regulation of the PI3K/Akt and Erk signaling pathways and the regulation of cell cycle proteins by REP could serve as effective strategies for improving pancreatic β-cell adhesion and proliferation. Abstract : Tissue engineering; Biomedical materials; Cell biology; Biotechnology; Diabetes; Insulin; -cell adhesion; -cell proliferation; RGD-modified elastin-like polypeptide; Cell cycle